2020
DOI: 10.1111/are.14973
|View full text |Cite
|
Sign up to set email alerts
|

Structural damage in liver, gonads, and reduction in spawning performance and alteration in the haematological parameter of Anabas testudineus by glyphosate‐ a herbicide

Abstract: The increasing demand for herbicides in agricultural fields affected aquatic environments as they entered into water bodies by agricultural runoff. Glyphosate (GLY), an organophosphate herbicide, is widely used in India for weed control. This study aimed to evaluate the toxic effects of GLY on climbing perch Anabas testudineus by studying its effects on the gonadosomatic index (GSI), hepatosomatic index (HSI), gonad and liver histology, spawning performance, and haematological parameters (RBC, WBC, haemoglobin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 47 publications
3
1
0
Order By: Relevance
“…In the present study in glyphosate-exposed fish, the liver showed degenerated hepatocytes, hyperplastic bile duct and congested hepatoportal blood vessels. The same histopathological picture was nearly noticed by Mohapatra et al (2021) Interestingly, fennel supplementation to glyphosate-exposed Nile tilapia in this study reversed the alterations in liver, oxidative stress and inflammatory markers towards the control values in a dose-dependent manner as seen in Tables 2 and 3 and supported with the histopathological results. Previous studies came in accordance with our results and suggested that fennel has hepatoprotective (Nazir et al, 2020), antioxidant (Al-Amoudi, 2017) and anti-inflammatory (Pacifico et al, 2018) properties based on the presence of polyphenols and flavonoids in its constituents.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study in glyphosate-exposed fish, the liver showed degenerated hepatocytes, hyperplastic bile duct and congested hepatoportal blood vessels. The same histopathological picture was nearly noticed by Mohapatra et al (2021) Interestingly, fennel supplementation to glyphosate-exposed Nile tilapia in this study reversed the alterations in liver, oxidative stress and inflammatory markers towards the control values in a dose-dependent manner as seen in Tables 2 and 3 and supported with the histopathological results. Previous studies came in accordance with our results and suggested that fennel has hepatoprotective (Nazir et al, 2020), antioxidant (Al-Amoudi, 2017) and anti-inflammatory (Pacifico et al, 2018) properties based on the presence of polyphenols and flavonoids in its constituents.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study in glyphosate‐exposed fish, the liver showed degenerated hepatocytes, hyperplastic bile duct and congested hepatoportal blood vessels. The same histopathological picture was nearly noticed by Mohapatra et al (2021) in Anabas testudineus , which was exposed to different concentrations of glyphosate for 45 days. Similarly, sublethal concentrations of di (2‐ethylhexyl) phthalate induced hepatic cell damage in Oreochromis mossambicus and Pseudetropus maculatus (Revathy & Chitra, 2015).…”
Section: Discussionsupporting
confidence: 81%
“…The presence of anisocytosis and poikilocytosis in Channa punctatus indicated toxic effects agrochemical on the red cell morphology due to pesticide impact (Mishra et al, 2017). Morphological deformations of RBC such as irregular margins, echinocytosis, lobopodial projections in response to toxicants were reported by various authors (Massar et al, 2012;Kaur and Kaur, 2015;Sadiqul et al, 2016;Mohapatra et al, 2021) and are in agreement with the findings of our present study.…”
Section: Haematological Analysissupporting
confidence: 94%
“…Glyphosate is a very toxic herbicide involved in the protection against common herbs grown on crop farms and is known for its carcinogenic effects (Van Bruggen et al 2018). Exposure to subchronic glyphosate led to oxidative stress, immunosuppression, inflammation, and apoptosis in various fish species (Ma et al 2019;Mohapatra et al 2021;Yalsuyi et al 2021). The accumulation of herbicides, pesticides, and insecticides in the farming water affects the gills, skin, and intestines tissues of fish as the first mucosal lines directly contact the surrounding water (Banaee et al 2020;Saha et al 2021;Yang et al 2020).…”
Section: Introductionmentioning
confidence: 99%